A path is emerging: Steps towards an LGBT+ inclusive education for Mexican students - Valderrábano, Jorge Herrera; Cai Thomas; Cody Freeman (Education Policy Analysis Archives, 2021)
Mexican schools are in crisis, where LGBT+ students face constant violence and discrimination. In the past decade, civil society has led the way in evaluating school climate and assessing LGBT+ students’ needs in Mexican schools. Unsurprisingly, individuals most affected by this violence and discrimination, LGBT+ individuals, have pushed these efforts forward as they conduct research, create resources, and facilitate workshops. In this article, we show how civil society has been the leader on advocating for LGBT+ inclusive education in Mexico. We justify this claim by exploring the existing research at the national, regional, and international levels, showing that much of what is present stems from civil society’s ongoing efforts. We then analyze the current legal framework aimed at protecting students against discrimination. We also discuss existing tools and advancements designed to promote inclusive classrooms, from both a public policy and civil society perspective. We conclude by punctuating the necessity and urgency of utilizing civil society in reforms that advocate for inclusion to better formulate public policies and establish direct, sustainable ties to the individuals and communities most in need.